Attestation before attention: unclaiming queer from Trương Tân's art (1990s-2010s) - Le, Ace Duc Phuong (Nanyang Technological University, 2022)
THROUGH the case study of Trương Tân – arguably one of the most misunderstood figures in Vietnamese contemporary art, this paper highlights the tendency to globalise and politicise queer artists from Southeast Asia via editorial and curatorial categorisation. By taking a contextualityoriented approach, it also aims to further bridge the academic gap between queer theory and art history, art criticism and curatorial practices in Vietnam. Archival content analysis found that Trương Tân has been consistently labelled as a queer artist who makes homoerotic art by media, galleries, institutions and scholars – either via explicit sensationalisation or implicit association – over the last three decades. Formal and comparative analysis found the artist’s most critical works to be multi-faceted across style, message and medium. A more holistic framework was then proposed to re-evaluate Trương Tân’s practices by looking at the converging identities of the subordinated – not specific to just the gay male – in his art, as they manifested along the multiplicity of anti-aesthetics aesthetics and exhibitive physicalities, and how such have evolved to subvert even themselves in the last three decades. When and where queer elements were detected, such were interpreted alongside the artist’s personal cultural, historical and socio-political contextualities. By dissecting the unsynchronised realities between the external attention on Trương Tân’s works and their intrinsic ground-breaking fundamentals, this paper problematises the lack of agency from artists in general – especially those from an underprivileged region – in framing and projecting their art within the globalised, capitalist dynamics of contemporary art.